Adobe Photoshop CC learn by video (2014 release) - McCathran, Kelly (Peachpit Press, 2014)
"This critically-acclaimed interactive training program from Adobe Press offers exceptional quality high-definition video to teach the fundamentals of Adobe Photoshop CC. Experienced instructor Kelly McCathran presents a compreshensive introduction to Photoshop, including best practices as well as fundamental photography and image editing concepts. Beginning with an overview of the Photoshop interface, Kelly goes on to cover Photoshop's powerful tools including new improvements to smart object and layer comps, features such as the Blur Gallery effects, Focus Mask, and more"--Resource description page.
Title from resource description page (viewed Oct. 1, 2014)
Keywords: Adobe Photoshop; Image processing -- Digital techniques; Traitement d'images; Techniques numériques; digital imaging; Image processing; Digital techniques; Electronic videos